2022
DOI: 10.1016/j.oooo.2021.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Image quality assessment of low-dose protocols in cone beam computed tomography of the anterior maxilla

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
(30 reference statements)
0
5
1
Order By: Relevance
“…13,15 Furthermore, there are recommendations to use low-dose protocols but without specifying resolution and other settings. 19 In the present study, the ULD and SD protocols did not exhibit any statistically significant difference in structure visibility in CBCT evaluation of an alveolar cleft before or after bone grafts. An unexpected tendency that ULD protocol had slightly higher scores in the visibility of cortical bone, trabecular bone, and periodontal space was noticed (Fig.…”
Section: Discussioncontrasting
confidence: 43%
See 4 more Smart Citations
“…13,15 Furthermore, there are recommendations to use low-dose protocols but without specifying resolution and other settings. 19 In the present study, the ULD and SD protocols did not exhibit any statistically significant difference in structure visibility in CBCT evaluation of an alveolar cleft before or after bone grafts. An unexpected tendency that ULD protocol had slightly higher scores in the visibility of cortical bone, trabecular bone, and periodontal space was noticed (Fig.…”
Section: Discussioncontrasting
confidence: 43%
“…Our results are in line with two previous in vitro studies. 18,19 Oenning et al compared low dose protocols in a preclinical setting using one pediatric anthromorphic phantom with different exposure settings of CBCT and concluded that a 45% decrease in radiation dose did not reduce the image quality. An in vitro study verified the image quality of the ULD protocol for structure visibility in the maxillary front region using eight phantoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations